Diet composition of Craugastor lineatus (Anura: Craugastoridae) of Chiapas, Mexico - Martínez-Coronel, Matías; Pérez-Gutiérrez, Marisol (Instituto de Ecología, A.C., 2011)
The ontogenetic and seasonal changes in the diet of Craugastor lineatus from Chiapas, México were described. We obtained 121 prey items from 54 stomachs by dissection, prey and prey parts were counted and identified to ordinal level. Twenty two food categories were identified. Frogs consumed mainly Aranae, Chilopoda, Coleoptera, Hymenoptera, Isopoda, Orthoptera, and plants, althoughthe representation of each category varied ontogenetically and temporally. The maximum length of the prey items was positively correlated with frog body size; meanwhile, the number of prey items was negatively correlated with frog body size. Juveniles consumed more Coleoptera and Isopoda, while adults captured more Aranae, Orthoptera and Chilopoda. Sixteen items were consumed in wet season, with Diptera, Isoptera, Lepidoptera and Acari as exclusive. During the dry season were ingested 18 items, with Phasmatoidea, Odonata, Psocoptera, Diplopoda and Pseudoescorpionida as exclusive.